Futurist arte / vita: Benedetta Fictionalized - Larkin, Erin (Volume 8 2018, 2018)
Keywords: dept.wll

Faunos en los trópicos: modernismo y virilidad - Hernández Rodríguez, Rafael (Ecos y resplandores helenos en la literatura hispana: siglos XVI-XXI, 2018, ISBN 978-84-697-9697-9, págs. 113-130, 2018)
Modernism represents an artistic movement that mirrors the changing society of the late 19th century. This changing society produced the first cultural and artistic movement in Spanish America that asked what was this region's place in the Western World as well as what the poet's new function was. Among other issues that revea) the modernity of the movement, such as urbanization, industrialization, or the role of women, there is one of capital importance: the view of masculinity. This essay focuses on three texts that review the image of masculinity and art thought the figure of the faun. El modernismo representa un movimiento artístico que refleja la sociedad cambiante de finales del siglo XIX. Esta sociedad cambiante genera el primer movimiento cultural y artístico continental de importancia que intenta responder a la pregunta ¿cuál es el lugar de Hispanoamérica en el mundo occidental y cuál es la nueva función del poeta? Entre otros aspectos que señalan la modernidad del movimiento (como el urbanismo, la industrialización, el papel de la mujer), hay uno de particular importancia: la revisión de la masculinidad. Este ensayo se centra en tres textos que revisan la visión de la masculinidad y el arte a través de la imagen del fauno.
Keywords: dept.wll

The Minor Tone of Desire - Barros, Pía; Cardone, Resha (Ediciones Sherezade, 2018)
Keywords: 21st century; Chilean fiction; Translations into English; Translations into English; Chilean fiction; Women authors; dept.wll; faculty_collection

Promoting social justice with CALL - Gleason, Jesse; Suvorov, Ruslan (CALICO Journal, 2018)
Keywords: dept.wll; peer-reviewed

Farewell to Naples: Ferrante’s 'Story of a New Name' - Palma, Pina (Forum Italicum: A Journal of Italian Studies, 2018)
In Ferrante’s Story of a New Name, the protagonist’s journey to self-knowledge and self-realization is mapped through a farewell trip to Naples before she begins her studies in Pisa. As the centerpiece and background around and against which Elena’s accomplishments, failures, and societal pressures revolve, Naples emerges as a mosaic of energy and lethargy, unbreakable traditions and negligible innovations. While these elements mirror the protagonist’s powerlessness in changing the “norms” to which she is expected to adhere, they also function as her spur to a steady shift toward self-understanding. In this article, I analyze the ways in which Ferrante’s use of the beauty and lure, corrosiveness and lethality of Naples parallel her discourse on the protagonist’s search for self-understanding, a process that will ultimately enable Elena, the protagonist, to find self-realization. © 2018, The Author(s) 2018.
Keywords: authorship; dept.wll; labyrinth; memory; peer-reviewed; reading; self-fulfillment; self-knowledge; urban space

Review of 'Ecological crisis and cultural representation in Latin America: Ecocritical perspectives on art, film and literature' - Flores, William (Hispania-a Journal Devoted to the Teaching of Spanish and Portuguese, 2018)
Keywords: dept.wll; peer-reviewed

The devil and the mirror: Pulci’s theology - Palma, Pina (Luigi Pulci in Renaissance Florence and Beyond, 2018)
Keywords: dept.wll

Connected classrooms: Videoconferencing in TESOL teacher preparation - Schmitt, Elena; Eilderts, Luke (International Journal of Teaching and Learning in Higher Education, 2018)
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found

Abundant student output through teachers’ big questions: A study in curricular design and teacher training - Verplaetse, Lorrie Stoops; Ferraro, Marisa; Mazzaro, M (TESOL Press Engaging Resources for Research - Elementary, 2018)
Keywords: dept.cur; dept.wll

Class, generation, and gender in Esther Tusquets's Habíamos Ganado La Guerra: Reflections on the winning of the Spanish Civil War - Weng, Miaowei (Hispanófila, 2018)
Keywords: dept.wll; peer-reviewed

El silencio abyecto en la plaza del diamante - Weng, Miaowei (Boletín Redipe, 2018)
The article examines the gender roles imposed on women in Spain under the Franco regime. It revisits Mercè Rodoreda’s 1962 novel The Time of the Doves and deciphers the female protagonist’s silence in the context of the post-Civil War period. Drawing on Julia Kristeva’s conception of the abject, it explores how silence becomes informative of the protagonist’s mental resistance to the patriarchal imposition, the helplessness and powerlessness a common woman feels under the Franco regime, and the gradual growth of female subjectivity.
Keywords: dept.wll; peer-reviewed; ⛔ No DOI found

Patterns of oral choice and evaluation across secondary content areas. - Gleason, Jesse; Berg, Margaret A; Huang, Jingzi (Language and Education, 2018)
Our study focuses on Choice and Evaluation, two of Mohan's knowledge structures to uncover how teachers and students across content areas developed disciplinary knowledge through classroom talk. Participants included in-service teachers and their students in rural and urban secondary schools in the Eastern and Western US. Through Choice and Evaluation, we examined opportunities for students across four disciplines to build up their knowledge of content matter or field. Findings revealed that teachers of math and science built students' field knowledge through classroom exploration, eliciting Evaluation in dialogic patterns involving Choice, while social studies and language arts teachers helped students implicitly use Choice/Evaluation through projects based on their previous experiences. The essential role of student background knowledge in enabling participation across different types of oral exchanges is shown. This study uncovers tendencies across classrooms and makes linguistically informed suggestions for teachers in the disciplines.
Keywords: Teacher education; classroom discourse; dept.wll; language across content; peer-reviewed

Evaluating teacher tech literacies using an argument-based approach - Gleason, Jesse; Schmitt, Elena (Assessment across online language education, 2018)
Keywords: dept.wll